Nurses versus physician-led interhospital critical care transport: a randomized non-inferiority trial - van Lieshout, Erik Jan (Intensive Care Med, 2016)
PURPOSE: Regionalization and concentration of critical care increases the need for interhospital transport. However, optimal staffing of ground critical care transport has not been evaluated. METHODS: In this prospective, randomized, open-label, blinded-endpoint non-inferiority trial, critically ill patients on mechanical ventilation transported by interhospital ground critical care transport were randomized between transport staffed by a dedicated team comprising a critical care nurse and paramedic (nurses group) or a dedicated team including a critical care physician (nurses + physician group). The primary outcome was the number of patients with critical events, both clinical and technical, during transport. Clinical events included decrease in blood pressure, oxygen saturation, or temperature, blood loss, new cardiac arrhythmias, or death. Non-inferiority was assumed if the upper limit of the two-sided 90 % confidence interval (CI) for the between-group difference lies below the non-inferiority margin of 3 %. RESULTS: Of 618 eligible transported critically ill patients, 298 could be analyzed after randomization and allocation to the nurses group (n = 147) or nurses + physician group (n = 151). The percentages of patients with critical events were 16.3 % (24 incidents in 147 transports) in the nurses group and 15.2 % (23 incidents in 151 transports) in the nurses + physician group (difference 1.1 %, two-sided 90 % CI [−5.9 to 8.1]). Critical events occurred in both groups at a higher than the expected (0–1 %) rate. In the nurses group consultations for physician assistance were requested in 8.2 % (12 in 147 transports), all of which were performed prior to transport. CONCLUSIONS: The number of patients with critical events did not markedly differ between critical care transports staffed by a critical care nurse and paramedic compared to a team including a critical care physician. However, as a result of an unexpected higher rate of critical events in both groups recorded by an electronic health record, non-inferiority of nurse-led interhospital critical transport could not be established (http://www.controlled-trials.com/ISRCTN39701540).